2014
DOI: 10.1021/jo500499g
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Selenoamide Dianions with Thio- and Selenoformamides Leading to the Formation of 5-Aminoselenazoles: Photophysical and Electrochemical Properties

Abstract: 5-Amino-2-selenazolines were synthesized by reacting selenoamide dianions generated from secondary selenoamides and BuLi with tertiary thio- and selenoformamides followed by treatment with iodine. The resulting 5-amino-2-selenazolines were further oxidized with iodine to give 5-aminoselenazoles in moderate to good yields. The general tendencies in the (77)Se NMR spectra of the starting selenoamides, 5-amino-2-selenazolines, and 5-aminoselenazoles were determined. The chemical shifts of these compounds were hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…The difference is further substantiated by the 77 Se NMR spectra, which exhibit a doublet of doublets in each case. The chemical shifts and coupling constants are comparable to the similar structures in the literature . Detailed NMR spectroscopic analysis and iterative simulation reveal the coupling constant between two phosphorus atoms ( 2 J (P,P) 9.4‐16.4 Hz) in 4–6 .…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The difference is further substantiated by the 77 Se NMR spectra, which exhibit a doublet of doublets in each case. The chemical shifts and coupling constants are comparable to the similar structures in the literature . Detailed NMR spectroscopic analysis and iterative simulation reveal the coupling constant between two phosphorus atoms ( 2 J (P,P) 9.4‐16.4 Hz) in 4–6 .…”
Section: Resultssupporting
confidence: 77%
“…In the 13 C NMR spectra of 4‐substituted‐1,3‐selenazol‐2‐amines 12–15 , the chemical shifts for the selenazole ring backbone carbon atoms fall in the range 167.3 to 169.3, 150.7 to 158.7, 100.6 to 108.7 ppm, respectively, these value are slightly lower than that in 4‐aryl‐1,3‐selenazoles [170.7 to 190.1, 153.7 to 159.6 and 109.4 to 127.1 ppm] . More interestingly, 77 Se NMR chemical shifts in 4‐substituted‐1,3‐selenazol‐2‐amines 12–15 range from 582.1 to 604.4 ppm, which are significantly lower than that in 2,4‐diaryl‐1,3‐selenazoles [705.5 to 798.8 ppm] and 5‐aminoselenazoles [629.0‐707.0 ppm] . The results indicated the high influence by the basic skeletons of selenazoles and the substituents close to the selenium atom .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…5,82.4,117.7,121.4,123.4,123.8,125.0,126.1,126.3,127.1,127.9,128.8,128.9,129.4,129.6,140.0,144.0,145.6,161.7;MS (EI) (4R*,5S*)-4,5-Dihydro-4-(2-methylphenyl)-N,N,2-triphenyl-5-thiazolamine (9).…”
Section: General Procedures For the Preparation Of Thiazolines To A Smentioning
confidence: 99%
“…[14,15] We have previously reported that the fluorescencep roperties of 5-N-arylaminothiazole 1 (Scheme 1) can be controlled by the substituents, andt hat the presence of electron-donating groups on the nitrogen atom at the 5-position bathochromically shifts the emission. [16] 5-Aminothiazole 1 contains monocyclic homo-a nd heteroaromatic groups,w hereby their conformation is intricately correlatedt ob oth solventa nd temperature.…”
mentioning
confidence: 99%